Impact of dissociation on treatment of depressive and anxiety spectrum disorders with and without personality disorders - Prasko, Jan; Grambal, Ales; Kasalova, Petra; Kamardova, Dana; Ociskova, Marie; Holubova, Michaela; Vrbova, Kristyna; Sigmundova, Zuzana; Latalova, Klara; Slepecky, Milos; Zatkova, Marta (Neuropsychiatric disease and treatment, 2016)
OBJECTIVE: The central goal of the study was to analyze the impact of dissociation on the treatment effectiveness in patients with anxiety/neurotic spectrum and depressive disorders with or without comorbid personality disorders. METHODS: The research sample consisted of inpatients who were hospitalized in the psychiatric department and met the ICD-10 criteria for diagnosis of depressive disorder, panic disorder, generalized anxiety disorder, mixed anxiety-depressive disorder, agoraphobia, social phobia, obsessive compulsive disorder, posttraumatic stress disorder, adjustment disorders, dissociative/conversion disorders, somatoform disorder, or other anxiety/neurotic spectrum disorder. The participants completed these measures at the start and end of the therapeutic program - Beck Depression Inventory, Beck Anxiety Inventory, a subjective version of Clinical Global Impression-Severity, Sheehan Patient-Related Anxiety Scale, and Dissociative Experience Scale. RESULTS: A total of 840 patients with anxiety or depressive spectrum disorders, who were resistant to pharmacological treatment on an outpatient basis and were referred for hospitalization for the 6-week complex therapeutic program, were enrolled in this study. Of them, 606 were statistically analyzed. Data from the remaining 234 (27.86%) patients were not used because of various reasons (103 prematurely finished the program, 131 did not fill in most of the questionnaires). The patients' mean ratings on all measurements were significantly reduced during the treatment. Also, 67.5% reached at least minimal improvement (42.4% showed moderate and more improvement, 35.3% of the patients reached remission). The patients without comorbid personality disorder improved more significantly in the reduction of depressive symptoms than those with comorbid personality disorder. However, there were no significant differences in change in anxiety levels and severity of the mental issues between the patients with and without personality disorders. Higher degree of dissociation at the beginning of the treatment predicted minor improvement, and also, higher therapeutic change was connected to greater reduction of the dissociation level. CONCLUSION: Dissociation is an important factor that influences the treatment effectiveness in anxiety/depression patients with or without personality disorders resistant to previous treatment. Targeting dissociation in the treatment of these disorders may be beneficial.
Keywords: personality disorders; PTSD; anxiety disorders; panic disorder; treatment resistance; depression; GAD; social phobia; OCD; adjustment disorders